Coincidence summing corrections using PENELOPE/PENNUC Monte Carlo code for volume sources of different densities. (February 2023) - Salpadimos, N.; Karfopoulos, K.; Seimenis, I.; Potiriadis, C.
Abstract: This work aims at providing a Monte-Carlo based methodology for calculating true coincidence correction (TCC) factors for volume sources of varying density. All simulations were carried out using the most recent version of Monte Carlo code PENELOPE. The main program PENMAIN was used for the calculation of full energy peak efficiencies. The subroutine PENNUC was utilized for the same calculation while taking summation effects into account. It was applied to Eu-152 and Cs-134 volume sources of 9 different densities, whilst the effect of the source's density on the TCC factor was investigated. There are differences between current results and the ones calculated by the TrueCoinc software. A relative bias up to 15% was observed, while the mean relative bias was 4.5%. The different approaches between the two codes could explain these deviations. Highlights: Utilization of PENELOPE for determining true coincidence correction factors. Calculation of true coincidence correction factors for different densities. Comparison with results from the software TrueCoinc. Investigation of the source's density in the true coincidence correction factor.